A Hypothesis: Linking Phase Separation to Meiotic Sex Chromosome Inactivation and Sex-Body Formation - Xu, Yiding; Qiao, Huanyu (Frontiers in Cell and Developmental Biology, 2021)
During meiotic prophase I, X and Y chromosomes in mammalian spermatocytes only stably pair at a small homologous region called the pseudoautosomal region (PAR). However, the rest of the sex chromosomes remain largely unsynapsed. The extensive asynapsis triggers transcriptional silencing - meiotic sex chromosome inactivation (MSCI). Along with MSCI, a special nuclear territory, sex body or XY body, forms. In the early steps of MSCI, DNA damage response (DDR) factors, such as BRCA1, ATR, and H2AX, function as sensors and effectors of the silencing signals. Downstream canonical repressive histone modifications, including methylation, acetylation, ubiquitylation, and SUMOylation, are responsible for the transcriptional repression of the sex chromosomes. Nevertheless, mechanisms of the sex-body formation remain unclear. Liquid-liquid phase separation (LLPS) may drive the formation of several chromatin subcompartments, such as pericentric heterochromatin, nucleoli, inactive X chromosomes. Although several proteins involved in phase separation are found in the sex bodies, when and whether these proteins exert functions in the sex-body formation and MSCI is still unknown. Here, we reviewed recent publications on the mechanisms of MSCI and LLPS, pointed out the potential link between LLPS and the formation of sex bodies, and discussed its implications for future research.